2019
DOI: 10.2174/1874944501912010284
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Intensity, and Factors Associated with Soil-Transmitted Helminths Infection among Children in Zambia: A Cross-sectional Study

Abstract: Background: Soil-transmitted helminths are among the neglected tropical diseases (NTDs) of poverty. They are a common type of parasitic infections in the world, caused by three main species commonly known as roundworms, whipworms, and hookworms. The diseases have major health and socio-economic repercussions and significantly contribute to public health problems in developing countries. Objectives: This study investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
2
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 22 publications
6
2
2
4
Order By: Relevance
“…Like other studies we were also found fruit and vegetable washing affected the prevalence of IPI [ 73 ], which might relate to the level of cleanliness and soil transmission risks. Open defecation and the availability latrines were other potential causes of IPI in our findings, which is similar to a study done in Zambia [ 71 ]. This finding could reflect that those communities who experience unclean environments due to open defecation are more likely to transmit parasites through soil, water, fomites, foods, or other means.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Like other studies we were also found fruit and vegetable washing affected the prevalence of IPI [ 73 ], which might relate to the level of cleanliness and soil transmission risks. Open defecation and the availability latrines were other potential causes of IPI in our findings, which is similar to a study done in Zambia [ 71 ]. This finding could reflect that those communities who experience unclean environments due to open defecation are more likely to transmit parasites through soil, water, fomites, foods, or other means.…”
Section: Discussionsupporting
confidence: 92%
“…This finding could reflect that educated mothers had better knowledge about IPI prevention and potentially better economic status enabling them to embrace the entire prevention process with available materials like soap/ash, water, shoes and other necessities. Additionally, in the current study, rural residents were 87% more likely to be infected by intestinal parasites, which is similar to findings from studies in Zambia and Nepal [ 71 , 72 ]. This situation may arise because rural community dwellers had lower awareness and more frequent contact with soil as well limited access to safe water and latrine.…”
Section: Discussionsupporting
confidence: 90%
“…was the most prevalent soil-transmitted helminth species in all the five selected communities and sampling biotopes. This confirms the cosmopolitan character of that species as previously largely documented [24,25]. This can be explained by the fact that its eggs can survive for several months in soil, even in adverse environmental conditions due to their inner shell being of a lipoprotein nature, which makes them resistant to drastic environmental conditions [26].…”
Section: Discussionsupporting
confidence: 86%
“…Like other studies we were also found fruit and vegetable washing affected the prevalence of IPI (75), which might relate to the level of cleanliness and soil transmission risks. Open defecation and the availability latrine were another potential cause of IPI in our ndings, which is similar to a study done in Zambia (73). This could re ect that those communities who experience unclean environments due to open defecation are more likely to transmit parasites through soil, water, fomites, food or other means.…”
Section: Abbreviationssupporting
confidence: 89%
“…This nding could re ect that educated mothers had better knowledge about IPI prevention and potentially better economic status enabling them to embrace the entire prevention process. Additionally, in the current study, rural residents were 87% more likely to be infected by intestinal parasites, which is similar to ndings from studies in Zambia and Nepal (73,74). This situation may arise because be rural community dwellers had lower awareness and more frequent contact with soil as well limited access to safe water and latrine.…”
Section: Abbreviationssupporting
confidence: 86%